PENEGAKAN HUKUM PIDANA TERHADAP PEMALSUAN PLAT NOMOR POLISI PADA PEMERIKSAAN KENDARAAN LALU LINTAS DI JALAN RAYA OLEH SATUAN LALU LINTAS POLISI RESOR KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - IMELDA '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Criminal law is present in the community as a means to eradicate crime in the comunity.associated with the authenticity of a plate operated motor vehicle on the road without the necessary license platenumber sign legitimate vehicle in accordance with a letter of explanation TNKB concered by articel 42 ayat 3 letter d of goverment Regulation Number 80 of 2012 on the inspection procedur motocycel vehicles on the road.eforcemen of traffic violations and road transport is a criminal offence, for biker both two wheels and four wheels that violatethe provisions of article 57 travif laws and road transport of vehicle accesories can be in prison terms or fines appropiate that has been set in article 280 of traffic laws and road transport set penalties for people who drive vehicles without fittedTNKB official in charge by the police.by law number 22 of 2009 on traffic and road transportthat the investigation and prosecution of traffic ofenses and road transport carried out by police investigators from the Republic of Indonesia and investigator of civil servants in the field of trafiic and road transport law eforcement againts violations of counterfeiting red plate set in the Regulation Number 3 of 2012 chapter 4 and 5 of the issuance of vehicle registration privileged and confidential for biker vehicle license issued by the IndonesiaPolice force is the vehicle registration priveleged and cofidental given to the offical vehicles, used by military police officers and govermentoficial vehicles which do not comply with the rules be penalized in accordance with article 280 jo 68 law number 22 of 2009 on trafic and road transport in the casse of forgery plate this new car that criminal provisions described in article 64 paragraph 2 of law number 22 year 2009 on trafic and road transport.Keywords : Criminal act-forgery-motorcycle vehicle license plate